Medical-surgical nursing critical thinking in patient care - LeMone, Priscilla; Burke, Karen M.; Bauldoff, Gerene (Pearson Education Limited, 2014)
Medical-Surgical Nursing: Critical Thinking in Patient Care, 5e has been revised and updated to provide the knowledge and skills needed to care for adult patients to promote health, facilitate recovery from illness and injury, and provide support when coping with disability or loss. Throughout the text, the authors make every effort to communicate that both nurses and patients may be male or female; and that patients require holistic, individualized care regardless of their age; gender; or racial, cultural, or socioeconomic background. The goal of the fifth edition is to provide the knowledge and resources that ensure a solid base for critical thinking and clinical judgment and that can be applied to provide safe, individualized, and competent clinical nursing care. Multiple learning strategies have been developed to facilitate success-audio, illustrations, teaching tips, and video and animation media. Understandable language and a consistent format are used, and students overwhelmingly report that they actually like reading the text.